2006
DOI: 10.1111/j.1360-0443.2006.01405.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological models of alcohol outlets and violent assaults: crime potentials and geospatial analysis

Abstract: Population and place characteristics are associated with rates of violence across spatial areas. Alcohol outlets directly affect and moderate potentials for violence associated with socio-demographic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
255
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(280 citation statements)
references
References 27 publications
17
255
3
Order By: Relevance
“…4,5 On the other hand, perceived or subjective availability has been found to be a better predictor of alcohol consumption than physical availability in some studies. 6,7 Alcohol outlet density has also been associated with a variety of social problems including violent assault, [8][9][10][11][12] alcohol-related motor vehicle accidents and fatalities, 12,13 and sexually transmitted disease rates. 14,15 Yet, other studies have found that drug-related crime is a stronger predictor of violence than alcohol outlets.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 On the other hand, perceived or subjective availability has been found to be a better predictor of alcohol consumption than physical availability in some studies. 6,7 Alcohol outlet density has also been associated with a variety of social problems including violent assault, [8][9][10][11][12] alcohol-related motor vehicle accidents and fatalities, 12,13 and sexually transmitted disease rates. 14,15 Yet, other studies have found that drug-related crime is a stronger predictor of violence than alcohol outlets.…”
Section: Introductionmentioning
confidence: 99%
“…Both the density of alcohol outlets and the density of drug crimes per capita can predict violent crime rates in those communities (Gorman, Zhu, & Horel, 2005). Other studies have also reported links between alcohol outlet density and assault rates (Gruenewald, Freisthler, Remer, LaScala, & Treno, 2006). High levels of alcohol availability in a community may increase rates of violence through behavioral dis-inhibition at the individual level, especially in contexts with existing norms supportive of violence, or by undermining social organization and collective efficacy in disadvantaged or high-risk communities (Nielsen, Martinez, & Lee, 2005).…”
Section: Availability Of Drugs/alcohol In Communitymentioning
confidence: 99%
“…While licensed premises play a key role in alcohol-related violence (Graham et al, 2001;Gruenewald et al, 2006), it is not easy to develop successful interventions in this area. Two recent reviews concluded that most of the evaluations of interventions implemented to reduce alcohol-related harm and overserving in drinking environments are limited because of methodological shortcomings (Jones et al, 2011;Kurtze et al, 2014).…”
Section: Introductionmentioning
confidence: 99%